First record of Aedes vittatus in Santiago de Cuba province - Mirtha Gladys Pérez Menzies; Rosa María Castillo Quesada; Yuneisy Alfonso Herrera (Medisan, 2022)
Aedes vittatus, vector that transmits the yellow fever virus, dengue, zika and chikungunya, was detected for the first time in January, 2020 in the town of Ramón de las Yaguas town from Santiago de Cuba municipality, what constituted the first record in the province with the same name. This finding meant an alert for the rest of the country and led to investigate on its bioecology and vectorial competence. To such effects the present study was carried out with the objective of informing everything related to the presence of this invading species, the space distribution and breeding sites to adopt preventive and control decisions.